A Semi-Quantitative Risk Assessment and Management Strategies on COVID-19 Infection to Outpatient Health Care Workers in the Post-Pandemic Period - Wang Y; Wang L; Zhao X; Zhang J; Ma W; Zhao H; Han X (Dove Medical Press, 2021)
Yuncong Wang, Lihong Wang, Xia Zhao, Jingli Zhang, Wenhui Ma, Huijie Zhao, Xu Han Hospital Infection Management Division, Xuan Wu Hospital Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Lihong WangDirector of Division of Hospital Infection Management Division, Xuan Wu Hospital Capital Medical University, No. 45 ChangChun Street, Xicheng District, Beijing, 100053, People’s Republic of ChinaTel +86 010 83198602Email 18618247182@163.comBackground: In the pandemic of COVID-19, due to asymptomatic patients and high personnel fluidity in outpatient clinics, health care workers (HCWs) in outpatients were facing severe threat from infection. There is an urgent need for a risk assessment to recognize and prevent infection risks.Purpose: To establish a semi-quantitative risk assessment model on COVID-19 infections for HCWs in outpatient departments, and apply it to practices. Further to provide infection risk management strategies to reduce infection threats in the post-pandemic of COVID-19.Methods: We used the method of Brainstorm, Literature study and Analytic Hierarchy Process (AHP) for risk factors selection and model construction, we also created corresponding indicators for each risk factors, in order to collect data in assessment practice.Results: Eighteen risk factors were recognized and selected for model construction, by scatter plot, these risk factors had been classified into four parts, spanned the scopes of diagnosis and treatment, environment, personal protection and emergency handling, with specific management suggestions provided. In the practice, outpatient clinics were divided into three risk levels, 5 clinics in high risk level, 9 in medium risk level and 11 in low risk level.Conclusion: A proper comprehensive risk assessment model for COVID-19 infections has been successfully established. With the model, the ability to COVID-19 prevention in outpatients can be easily evaluated. The strategies on disinfection, surveillance and personal protection were also valuable references in the post-pandemic of COVID-19.Keywords: COVID-19, health care workers; HCWs, outpatient, risk assessment